(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2024)
This report refers to three lambe-lambe theaters that have death as a dramaturgical principle: Mistérios de Elêusis, A Visita and Gato Negro. Mistérios de Elêusis is a trilogy about the myth of Persephone, ruling goddess of the world of the dead. A Visita and Gato Negro were part of the Instantes de Passagem project, a sextet of lambe-lambe theaters about the intimate moment of death. All three lambe-lambe theaters use a digital projector as a technical resource for scenic composition.